The Ketepatan Penyimpanan Obat High Alert Medication di Instalasi Farmasi RSUD Dr. Soegiri Lamongan: Penyimpanan Obat High Alert Medication di Instalasi Farmasi RSUD Dr. Soegiri Lamongan; Ketepatan Penyimpanan Obat High Alert Medication - Rahmadinah, Hifar (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2024)
Rahmadinah, H. 2022. Accuracy of Storage of High Alert Medication in the PharmacyInstallation of RSUD Dr. Soegiri Lamongan 2022. Thesis. Pharmacy StudyProgram, Faculty of Medicine and Health Sciences, Maulana Malik IbrahimState Islamic University, Malang. Supervisor I : apt. Hajar Sugihantoro,S.Farm., M.P.H.; Supervisor II : apt. Ah. Syahrir, M. Farm.High Alert Medication (HAM) is a group of drugs that need to be watched out for in theiruse because they can lead to high use of unwanted drugs (Medication Error). The highalert medication group is divided into LASA (Look A Like Sound A Like) drugs, highlyconcentrated electrolytes, and cytostatics (cancer drugs). The purpose of this study was todetermine the profile and accuracy of storage of LASA (Look A Like Sound A like)drugs and high-concentrate electrolytes based on the issued SOPs. This research includesdescriptive research by observing, classifying, recording, and analyzing with SOPguidelines. The sample of this study used LASA (Look A Like Sound A Like) drugs andhighly concentrated electrolytes. Location The research was conducted at the pharmacyinstallation of RSUD Dr. Soegiri Lamongan in 2022. The results show that the storageprofile of LASA (Look Alike Sound A Like) and high concentrate electrolytes uses astorage method based on the storage method based on the form and type ofpharmaceutical preparations, FIFO, FEFO, and alphabetically. The storage accuracy ofLASA drugs (Look Alike Sound A Like) for indicators of separated LASA drugs withtheir equivalents is 97.72% and LASA drugs labeled "LASA" with a yellow base is90.9%. Accuracy of high-concentrated electrolyte drug storage for indicators Highconcentrated electrolyte medicine is labeled “High Alert” at 100% and high-concentratedelectrolyte medicine is labeled “Concentrated Electrolyte” with a yellow base color of100%. Based on these results, it can be concluded that the LASA (Look Alike Sound ALike) storage has not met the accuracy based on the issued SOP.Keywords : LASA (Look A Like Sound A Like), high concentrate electrolyte,Medication Error